Using Gauss - Jordan elimination method with The Application of Android for Solving Linear Equations - Hasanudin, Muhaimin; Kristiadi, Dedy Prasetya; Yuliana, Khozin; Tarmizi, Rasyid; Kuswardani, Dwina; Abdurrasyid, A (Universitas Malikussaleh, 2019)
Problems involving mathematical models appear in many scientific disciplines. Complex mathematical models sometimes cannot be solved by analytic methods using standard algebraic formulas. Computers play a major role in the development of the field of numerical methods because the calculation uses numerical methods in the form of arithmetic operations, the number of arithmetic operations is very large and repetitive, so manual calculations are often tedious and errors occur. This study aims to develop software solutions for linear equations by implementing the Gauss-Jordan elimination(GJ-elimination) method, building software for linear equations carried out through five stages, namely: (1) System Modeling (2) Simplification of Models, (3) Numerical Methods and algorithms, (4) programming languages using The Android Studio and (5) Simulation programs. Overall regarding content, proper software that can be used by students and lecturers in implementing numerical methods because there are ways to use the application and steps to solve linear equation problems using the GJ-elimination method.